Linguistic agency assignment in The Star Online headlines on COVID-19 - Adlina Ariffin,; Fakhira Jafri, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The media coverage on the COVID-19 pandemic has caused emotional distress among people. This calls for a close scrutiny of health-related information on COVID-19 disseminated via news headlines. It is essential to determine which context – risk, prevention, or treatment – needs to be emphasised in covering news related to a pandemic and whether such reporting leads to public health scare or health consciousness. This paper discusses a study which investigated this issue by adopting Linguistic Agency Assignment as the framework in analysing COVID-19 related news headlines of a Malaysian mainstream news outlet, The Star Online. Extended Parallel Process Model (EPPM) was used to examine whether the writings induced fear or created awareness among the public. Findings of the thematic and textual analysis of a corpus of news headlines revealed that the Malaysian mainstream newspaper often disseminated prevention-themed messages related to COVID-19, used more human agency language, and induced fear in the audience, while at the same time, delivered a high level of COVID-19 awareness to readers.